2007
DOI: 10.1213/01.ane.0000287248.25610.c0
|View full text |Cite
|
Sign up to set email alerts
|

Low-Dose Intravenous Midazolam Reduces Etomidate-Induced Myoclonus: A Prospective, Randomized Study in Patients Undergoing Elective Cardioversion

Abstract: IV midazolam 0.015 mg/kg administered 90 s before induction of anesthesia with etomidate is effective in reducing myoclonic movements and does not prolong recovery in unpremedicated patients after short procedures.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
47
1
1

Year Published

2010
2010
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 65 publications
(51 citation statements)
references
References 15 publications
2
47
1
1
Order By: Relevance
“…Although the mechanism of the myoclonus is not clear, benzodiazepines, opioids, and rocuronium have been used as pretreatments to reduce etomidate-induced myoclonus [6][7][8][9][10]. However, no published data are yet available about the effects of lidocaine on myoclonus after injection of etomidate.…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…Although the mechanism of the myoclonus is not clear, benzodiazepines, opioids, and rocuronium have been used as pretreatments to reduce etomidate-induced myoclonus [6][7][8][9][10]. However, no published data are yet available about the effects of lidocaine on myoclonus after injection of etomidate.…”
mentioning
confidence: 99%
“…Also, in recent research Choi et al [16] showed that pretreatment with rocuronium significantly reduced the frequency of myoclonus due to etomidate by blocking transmission at the neuromuscular junction. But clinically distressing side effects are frequently observed, for example sedation, apnea, chest muscle rigidity, cardiovascular depression for opioids, delayed recovery for benzodiazepines, and airway obstruction, regurgitation, and aspiration for muscle relaxants [10,13,16]. An ideal pretreatment drug for preventing myoclonic movements should be shortacting, not have significant effects on respiration and hemodynamics, and not prolong recovery from anesthesia [10].…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…They concluded that pretreatment with midazolam is effective in reducing the incidence of myoclonic movements while preserving the advantage of etomidate; that is, cardiovascular stability and short duration of action [3]. Huter et al investigated the effects of low dose intravenous midazolam pretreatment 0.015 mg/kg on the incidence and severity of myoclonus during induction of anaesthesia with etomidate for elective cardioversion in un-premedicated patients and it was found that 10% of patients in midazolam group had myoclonic movements as compared to 50% receiving placebo [10].…”
Section: Discussionmentioning
confidence: 99%
“…Pain on injection has been abolished by the new fat emulsion of etomidate, but the new solvent has not reduced the incidence of myoclonus [2]. Myoclonus is a common problem during induction of anesthesia with etomidate; up to 80% of non-premedicated patients develop myoclonic movements, [3] which may be a problem in the non-fasting patient because of the risk of hypoventilation as well as theoretically regurgitation and aspiration [4,5]. In patients with an open globe injury, myoclonus after etomidate raises the risk of prolapse of vitreous material as a result of high intraocular pressure [6].…”
Section: Introductionmentioning
confidence: 99%